A User Study on MR Remote Collaboration Using Live 360 Video - Lee, Gun A.; Teo, Theophilus; Kim, Seungwon; Billinghurst, Mark (2018 IEEE International Symposium on Mixed and Augmented Reality (ISMAR), 2018)
Sharing and watching live 360 panorama video is available on modern social networking platforms, yet the communication is often a passive one-directional experience. This research investigates how to further improve live 360 panorama based remote collaborative experiences by adding Mixed Reality (MR) cues. SharedSphere is a wearable MR remote collaboration system that enriches a live captured immersive panorama based collaboration through MR visualisation of non-verbal communication cues (e.g., view awareness and gestures cues). We describe the design and implementation details of the prototype system, and report on a user study investigating how MR live panorama sharing affects the user's collaborative experience. The results showed that providing view independence through sharing live panorama enhances co-presence in collaboration, and the MR cues help users understanding each other. Based on the study results we discuss design implications and future research direction.